Strategi Pengembangan Instalasi Farmasi Rumah Sakit Tingkat IV Slamet Riyadi Surakarta Dengan Metode SWOT - Hartono Hartono; Gunawan Pamudji Widodo; Elina Endang Sulistyowati (Jurnal Farmasi Indonesia, 2011)
Decree of the Minister of Health No. 1197/Menkes/SK/X/2004 on Standards of Hospital Pharmacy Services, which states that the hospital pharmacy services is an integral part of hospital health care system is oriented to patient care, the provision of quality medicines, including clinical pharmacy services, are affordable for all levels of society. Installation of Hospital Pharmacy is the only division of hospitals that are fully responsible for the management and control throughout the pharmaceutical and other medical supplies in circulation and used in hospitals. In this regard the management and management of IFRS must be done properly, efficiently and effectively to support health services in hospitals. For that IFRS need to create appropriate strategies that began by analyzing both internal and external environment, known as SWOT analysis. Based on the SWOT analysis of the IFRS can formulate strategies that can be implemented in the service in IFRS. This type of research is a case study using descriptive research design and strategic analysis, with qualitative and quantitative approach that aims to explore the internal and external environmental conditions IFRS TK.IV Slamet Riyadi. Data were collected through observation of documents, direct observation and questionnaire spread. Qualitative data and quantitative data were analyzed contents were statistically analyzed. The results show the calculation results of internal evaluation matrix, the strength of IFRS Tk. IV Slamet Riyadi Surakarta is greater than the value of 0.28 weaknesses. The results of the evaluation matrix external factors also value the opportunities greater than the threat value of 0.25. Thus IFRS Tk. Slamet Riyadi Surakarta is at quadrant 1 which supports an aggressive growth policy. The selection strategy of using the matrix QSP results that improve the quality and quantity of human resources at 7.52; improved management of pharmaceutical supplies for 7.44; improving the quality of facilities, infrastructure and science and technology facility at 7.37; and the conduct of research, comparative studies and development hospital pharmacy installation of 7.29.